Relations between Paris and Berlin in the 1920s in Light of the First World War - I. E. Magadeev (Vestnik MGIMO-Universiteta, 2014)
The central question of the article - how the long-term consequences of the First World War influenced the French foreign policy in relation to Germany in the 1920s. Basing on the archival and published French diplomatic sources the author analyses the French political course after 1918 and after 1945 in the comparative way with the attention to the elements of continuity and change in the Paris' conception relating to the over-Rhine neighbor.